Decisão estrutural de apoio às escavações de mineração: Efeito do arco aplicando lógica paraconsistente anotada com dois valores em engenharia computacional - Souza, Paulo Roberto Schroeder (2018)
This work intends to establish a relationship of solutions by applying Paraconsistent Logic Applied (LPA) in establishment of arches surrounding pressure of underground excavations in massive fractured, considering the hypothesis that such independent dimensions arise with arches of span between pillars or support structures and structural conditions are primarilydependent of the Massif, in the State of active strains , the form of the excavations and the angle of internal friction of the material. The considerations to be developed do not consider the effects of plate tectonics that expresses so catastrophic as earthquakes or extremely high voltage fields, in that it would not be feasible for reasons of safety or economy the lavra of ore or mineral raw materials. Emphasizes the need of scientific-technical research applying concepts of LPA for the definition of relationships that allow knowledge of go set between support points of pressure arc and concludes by discussing how developments can occur in view of the dynamic aspect of mining excavations.